2014
DOI: 10.1021/ja412309j
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics and Thermodynamics of H/H•/H+ Transfer from a Rhodium(III) Hydride

Abstract: The thermodynamics and kinetics of all three cleavage modes for Rh-H, the transfer of H(-), H(+), or H•, have been studied for the Rh(III) hydride complex Cp*Rh(2-(2-pyridyl)phenyl)H (1a). The thermodynamic hydricity, ΔG°H(-), for 1a has been measured (49.5(1) kcal/mol) by heterolytic cleavage of H2 with Et3N in CH3CN. The transfer of H(-) from 1a to 1-(1-phenylethylidene)pyrrolidinium is remarkably fast (kH(-) = 3.5(1) × 10(5) M(-1) s(-1)), making 1a a very efficient catalyst for the ionic hydrogenation of im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
111
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 73 publications
(115 citation statements)
references
References 96 publications
(89 reference statements)
4
111
0
Order By: Relevance
“…Although the Phytopiithora isolates examined primarily came from established collections maintained by the authors and did not come from surveys conducted specifically for this study, most of the predominant species associated with ornamental plants are well-established pathogens of ornamental crops (10,23,26,27,29,32,37,45,47,51,52). Although the Phytopiithora isolates examined primarily came from established collections maintained by the authors and did not come from surveys conducted specifically for this study, most of the predominant species associated with ornamental plants are well-established pathogens of ornamental crops (10,23,26,27,29,32,37,45,47,51,52).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Although the Phytopiithora isolates examined primarily came from established collections maintained by the authors and did not come from surveys conducted specifically for this study, most of the predominant species associated with ornamental plants are well-established pathogens of ornamental crops (10,23,26,27,29,32,37,45,47,51,52). Although the Phytopiithora isolates examined primarily came from established collections maintained by the authors and did not come from surveys conducted specifically for this study, most of the predominant species associated with ornamental plants are well-established pathogens of ornamental crops (10,23,26,27,29,32,37,45,47,51,52).…”
Section: Discussionmentioning
confidence: 99%
“…To ensure that results from the 48-well culture plate assay were directly comparable with results from the standard petri plate assay, 43 isolates of P. nicotianae from ornamental plants and irrigation water (12 from North Carolina and 31 from Virginia) were screened with the 48well method, and these results were compared with those from the petri plate assay that were published previously (24,26,36,37). To ensure that results from the 48-well culture plate assay were directly comparable with results from the standard petri plate assay, 43 isolates of P. nicotianae from ornamental plants and irrigation water (12 from North Carolina and 31 from Virginia) were screened with the 48well method, and these results were compared with those from the petri plate assay that were published previously (24,26,36,37).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…[8] The authors reported that H 2 can replace the weakly bound acetonitrile ligand of the rhodiumc omplex, leading to H 2 coordination at the metal center.I nt he presence of an appropriate Lewis base, the H 2 molecule is cleaved heterolytically.I nt he approach chosen in this work, the Lewis base is aN 2 -containing tungsten pincer complex (see below). Norton and co-workersr eported the use of this rhodiumc omplex to cleave H 2 andh ydrogenateo rganic substrates.…”
mentioning
confidence: 99%